Tragedi Talangsari: Pelanggaran HAM yang Meninggalkan Luka di Lampung Timur Tahun 1989-2023 - Mutiara Angelika Harianja; Fransiska Dewi Setiowati Soenaryo; Anak Agung Inten Asmariati (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2023)
Bangli Regency which has one of the tourist villages located in Tembuku Village which has very potential tourism potential to be developed.The economy of Tembuku Village is driven by several sectors, and one of the most prominent so far is the Tourism Sector.The purpose ofthisresearchis to find out and understand problems related to the development of Pariwsata Tembuku Village, Bangli Regency in 2016-2022 using qualitative methods.The results of the research that can be put forward are as follows.1.) The background of tourism development in Tembuku Village will never be separated from the various roles of the community, village officials, tourism offices, the private sector and alsofrom various universities in the process of developing tourist attractions in Tembuku Village2.) The implications for the existence of natural water tourism in Tembuku Village in form of Tukad Cepung, Krisik Waterfall, Goa Giri Campuhan Waterfall have provided many benefits for the growth of Tembuku Village, especially in the economic, social, and cultural fields, namely increasing income, changing the livelihood system and thinking of the surrounding community